2017
DOI: 10.1007/s00296-017-3904-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient and physician perspectives on the impact of health-related quality of life in Mexican patients with ANCA-associated vasculitis

Abstract: The objective of this study is to describe aspects of health-related quality of life (HRQOL) in Mexican patients with antineutrophil cytoplasmic-associated vasculitis (AAV). Cross-sectional comparison study includes patients with established AAV and a comparison group with rheumatoid arthritis (RA), chronic kidney disease (CKD), and healthy subjects. Variables considered were: socio-demographic data, comorbidities, laboratory, disease activity, damage, and Physician's and Patient's Global Assessment (PhGA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Corresponding funnel plot shown in supplementary materials however, report a significant association between PHQ-9 and fatigue (r = 0.73, p < 0.05). Hinojosa-Azaola et al also found an association between HADS and fatigue (r = 0.48, p = 0.01) among AAV patients [27]. When they dichotomised HADS scores (threshold > 7), those with depression or anxiety had more steroid use (prednisolone ≥ 10 mg/ day; OR 6.65, 95% CI 1.37-32) than those without.…”
Section: Associations Between Depression and Disease Outcomesmentioning
confidence: 89%
See 1 more Smart Citation
“…Corresponding funnel plot shown in supplementary materials however, report a significant association between PHQ-9 and fatigue (r = 0.73, p < 0.05). Hinojosa-Azaola et al also found an association between HADS and fatigue (r = 0.48, p = 0.01) among AAV patients [27]. When they dichotomised HADS scores (threshold > 7), those with depression or anxiety had more steroid use (prednisolone ≥ 10 mg/ day; OR 6.65, 95% CI 1.37-32) than those without.…”
Section: Associations Between Depression and Disease Outcomesmentioning
confidence: 89%
“…Hajj-Ali et al also reported a higher prevalence of depression among GPA patients when compared to the general population (22 vs 7.6%; p < 0.001) [13]. Hinojosa-Azaola et al reported a numerically higher prevalence of depression in AVV patients (9%) than RA (4%) and CKD (1%) controls, although this was not statistically significant (p = 0.29) [27]. Basu et al found no significant difference in depression (BDI ≥ 13; AAV 15% vs primary care controls 21%; p = 0.50) [19].…”
Section: Depression Compared Between Psv and Controlsmentioning
confidence: 94%
“…This healthcare burden was expected in FVG considering the becoming into a chronic disease of AAV, thanks to improvements in treatment. Emerging evidence in other studies [10,33] is the negative effect on patients' physical and mental quality of life (QoL) of AAV, comparable to other chronic diseases. Current vasculitis disease assessment tools (BVAS v3 and VDI) are only weakly correlated with measures and variations of QoL [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Patients included in the present study participated in a crosssectional comparison analysis conducted to assess patient and physician perspectives on HRQOL in patients with AAV (Hinojosa-Azaola et al, 2018). Inclusion criteria were patients >18 years old with established diagnosis of AAV (GPA, MPA, or RLV) according to the American College of Rheumatology (ACR) 1990 or the definition by the 2012 Chapel Hill Consensus (Jennette et al, 2013;Leavitt et al, 1990).…”
Section: Study Patientsmentioning
confidence: 99%